MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS LINGKUNGAN - Nismawati Nismawati; Hepsi Nindiasari; Anwar Mutaqin (Universitas Sultan Ageng Tirtayasa, 2019)
The ability of mathematical reflective thinking is the ability to interpret a case based on the mathematical concepts involved, can evaluate the truth of an argument, can draw analogies from two similar cases, can analyze and clarify questions and answers, can generalize, and can distinguish between relevant data and not relevant. This ability is one of the high-level thinking skills that can be optimized through integrated learning in everyday life, namely learning with Environmental Based Problem Based Learning. To find out, a quasi-experimental study was conducted which aimed to find out the improvement of mathematical reflective thinking skills in terms of the high, medium and low mathematical abilities of the group. The subject of the research was class XI in SMA Negeri 1 Cilegon which was selected by cluster random sampling in the sequence and series material. The results of the data analysis showed that the Environmental Based Problem Based Learning model was better than the expository learning in improving the achievement and improvement of students' mathematical reflective thinking skills both viewed as a whole and viewed from the initial high, medium and low mathematical abilities. Keywords: Ability Of Mathematical Reflective Thinking, Environment-Based Problem Based Learning